2014
DOI: 10.1177/0193841x14524956
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Panel Management

Abstract: Many psychological processes unfold over time, necessitating longitudinal research designs. Longitudinal research poses a host of methodological challenges, foremost of which is participant attrition. Building on Dillman’s work, we provide a review of how social influence and relationship research informs retention strategies in longitudinal studies. Objective: We introduce the tailored panel management (TPM) approach, which is designed to establish communal norms that increase commitment to a longitudinal stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Estrada et al [ 24 ] suggested that panels can be seen as a form of social community. As such, those with a low sense of belonging may recognise this and participate to bolster their sense of belongingness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrada et al [ 24 ] suggested that panels can be seen as a form of social community. As such, those with a low sense of belonging may recognise this and participate to bolster their sense of belongingness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, social processes are central to many theories on panel management. Estrada, Woodcock, and Wesley Schultz [ 24 ], for example, have developed Tailored Panel Management (TPM) as an approach to longitudinal research design that emphasizes the ‘communal exchange’ between researcher and participant. They suggest that the panel represents a social community and that participation is an act of reciprocity built on established norms (that is, responding at the researcher’s request).…”
Section: Introductionmentioning
confidence: 99%
“…Participants completed baseline measures in 2005 and have completed online surveys twice per year concerning their educational/career status and aspirations, academic performance, and a number of psychological measures, including their perceived level of stereotype threat and achievement goal orientations. Survey response rates range from 68% to 84% (Estrada, Woodcock, & Schultz, 2014). We collected data for all variables at each point in time (see Online Supplemental Materials for treatment of missing data).…”
Section: Methodsmentioning
confidence: 99%
“… 1 The sample was recruited and maintained by the Tailored Panel Management (TPM) design, a methodology developed to manage longitudinal research designs (Estrada, Woodcock and Schultz 2014). TPM is designed to increase response rates and reduce attrition of panel participants by increasing the participant's commitment to the study.…”
mentioning
confidence: 99%